2018
DOI: 10.1111/trf.14970
|View full text |Cite
|
Sign up to set email alerts
|

Platelet α‐granules modulate the inflammatory response under systemic lipopolysaccharide injection in mice

Abstract: BACKGROUND Beyond their role in hemostasis and thrombosis, platelets are also important mediators of inflammation by the release of hundreds of factors stored in their α‐granules. Mutations in Nbeal2 cause gray platelet syndrome (GPS), characterized by the lack of platelet α‐granules. This study aims to evaluate the immunological (proinflammatory) effects of platelet α‐granules. STUDY DESIGN AND METHODS We performed an experiment using Nbeal2−/− mice, the mouse model of GPS. Systemic inflammation was induced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Female patients also exhibited reduced levels of IL-1 β when compared with male patients, a proinflammatory cytokine considered a potential target for COVID-19 therapy ( 34 ). Other proinflammatory transcripts (neurobeachin-like 2 [ NBEAL2 ]) critical for leukocyte recruitment and granule exocytosis ( 35 , 36 ) or alarmins that are released during tissue damage (S100 calcium binding protein A9 [ S100A9 ]) ( 37 , 38 ) were lower in swabs from female patients infected with SARS-CoV-2 in comparison with male patients. The differential expression analysis between female and male samples, both SARS-CoV-2–negative groups, showed downregulation of several genes belonging to the CMSP term ( Supplemental Figure 7, A and B ).…”
Section: Resultsmentioning
confidence: 99%
“…Female patients also exhibited reduced levels of IL-1 β when compared with male patients, a proinflammatory cytokine considered a potential target for COVID-19 therapy ( 34 ). Other proinflammatory transcripts (neurobeachin-like 2 [ NBEAL2 ]) critical for leukocyte recruitment and granule exocytosis ( 35 , 36 ) or alarmins that are released during tissue damage (S100 calcium binding protein A9 [ S100A9 ]) ( 37 , 38 ) were lower in swabs from female patients infected with SARS-CoV-2 in comparison with male patients. The differential expression analysis between female and male samples, both SARS-CoV-2–negative groups, showed downregulation of several genes belonging to the CMSP term ( Supplemental Figure 7, A and B ).…”
Section: Resultsmentioning
confidence: 99%
“…Females also exhibited reduced levels of IL-1β when compared to male patients, a pro-inflammatory cytokine considered a potential target for COVID-19 therapy 27 . Other pro-inflammatory transcripts (neurobeachin like 2, NBEAL2 ) critical for leukocyte recruitment and granule exocytosis 28,29 or alarmins that are released during tissue damage (S100 Calcium Binding Protein A9, S100A9 ) 30,31 were lower in swabs from females infected with SARS-CoV-2 in comparison to males. Multivariate regression analysis indicated that the expression of genes shown in Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Platelets (PLT) play a central role in haemostasis, and their role in modulating the inflammatory response is increasingly recognized [12][13][14][15]. PLT and fibrinogen are important substrates needed for clot formation.…”
Section: Discussionmentioning
confidence: 99%